2011
DOI: 10.1098/rspb.2011.1550
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism breakdown in breadfruit domestication

Abstract: During the process of plant domestication, below-ground communities are rarely considered. Some studies have attempted to understand the changes in root symbionts owing to domestication, but little is known about how it influences mycorrhizal response in domesticated crops. We hypothesized that selection for above-ground traits may also result in decreased mycorrhizal abundance in roots. Breadfruit (Artocarpus sp.) has a long domestication history, with a strong geographical movement of cultivars from west to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 62 publications
1
38
1
Order By: Relevance
“…Indeed, for soybean it has been shown that older cultivars rely more on nitrogen-fixing rhizobia than newer cultivars (Kiers et al 2007). Likewise, some wheat varieties appear to have become less dependent on AMF through time (Sawers et al 2008), and the same has been observed in breadfruit (Xing et al 2012). However, a recent meta-analysis across studies published over a period of 20 years concluded the opposite; the authors found that responsiveness to AMF has, in fact, increased with year since release (Lehmann et al 2012).…”
Section: Breeding Effects On Symbiotic Interactionsmentioning
confidence: 87%
“…Indeed, for soybean it has been shown that older cultivars rely more on nitrogen-fixing rhizobia than newer cultivars (Kiers et al 2007). Likewise, some wheat varieties appear to have become less dependent on AMF through time (Sawers et al 2008), and the same has been observed in breadfruit (Xing et al 2012). However, a recent meta-analysis across studies published over a period of 20 years concluded the opposite; the authors found that responsiveness to AMF has, in fact, increased with year since release (Lehmann et al 2012).…”
Section: Breeding Effects On Symbiotic Interactionsmentioning
confidence: 87%
“…Axis 1 agricultural settings, where cultivars have been shown to vary in AMF diversity or community composition (Xing et al 2012;Lebron et al 2012). Bever et al (1996) did not observe an effect of host genotype in their studies of grassland spore community composition.…”
Section: Axismentioning
confidence: 90%
“…Breadfruit, Artocarpus altils in Oceania are seedless and dependent upon humans for dispersal (Xing et al, 2012). Domesticated lupines, Lupinus spp., set seed earlier, produce larger seeds than wild lupines (Berger et al, 2017).…”
Section: Human Selectionmentioning
confidence: 99%